Kedudukan Anak Perempuan dalam Mewaris pada Masyarakat Batak Toba di Desa Simpang Mesuji - Indri Ati Sidabalok, Harni; Amir, Diana; Manik, Herlina (Universitas Jambi, Fakultas Hukum, 2023)
In the Toba Batak Indigenous People (patrilineal kinship) the position of men is very prominent and strong, so that the heirs in the Toba Batak Indigenous People are only men, not women because girls will marry and leave their relatives. However, there have been developments and changes to the inheritance of the Toba Batak Community which have occurred due to various factors. Research objectives 1) To find out and analyze the position of daughters in inheriting in the Toba Batak Community in Simpang Mesuji Village, Simpang Pematang District, Mesuji Regency, Lampung Province and 2) To find out and analyze the factors that influence changes in inheritance distribution in the Toba Batak Community in Simpang Mesuji Village Simpang Pematang District, Mesuji Regency, Lampung Province. The research uses empirical legal research methods, to see how the law works in society. Girls have a position in inheriting to the Toba Batak Community in Simpang Mesuji Village, Simpang Pematang District, Mesuji Regency, Lampung Province. The factors that influence the changes in the division of inheritance in the Toba Batak Community in the village are the factors of education, religion, justice, and compassion.